Identifikasi Qanun Aceh dalam Upaya Menumbuhkan Iklim Usaha Menuju Demokrasi Ekonomi Berdasarkan UUD Tahun 1945 - Eddy Purnama; Teuku Ahmad Yani; Saiful Bahri (Kanun Jurnal Ilmu Hukum, 2010)
ABSTRACT: This research to present whether economic democration as Stated in the 1945 Constotution, Article 33, has been able to be operationalized in to the Qanuns of Aceh for developing production athmosphir. This research refers secondary data, such as primary, secondary, tertiary resources. However emperical data was also used for quiding analysis of the research. Research finding shows that the effort of developing production athmosphir in case of the special authonomy in Aceh through regional and procedures regulation was not effectively achieved. This was indicated by unability of Aceh Government in constructing legislations product either for implementing obligation affairs or section of choices as there were mentioned in law Number 11, 2006 on Government of Aceh. Besides, effort of making debeaurocratization in permit services, it was not regulated yet in Qanun of Aceh. Identification for Qanun of Aceh in Developing Production Athmosphir Toward Economic Democration Based on 1945 Constitution